Achievements and Lessons Learned From Successful Small Satellite Missions for Space Weather‐Oriented Research. Issue 7 (25th July 2022) - Spence, Harlan E.; Caspi, Amir; Bahcivan, Hasan; Nieves‐Chinchilla, Jesus; Crowley, Geoff; Cutler, James; Fish, Chad; Jackson, David; Jorgensen, Therese Moretto; Klumpar, David; Li, Xinlin; Mason, James P.; et al.
Abstract: When the first CubeSats were launched nearly two decades ago, few people believed that the miniature satellites would likely prove to be a useful scientific tool. Skeptics abounded. However, the last decade has seen the highly successful implementation of space missions that make creative and innovative use of fast‐advancing CubeSat and small satellite technology to carry out important science experiments and missions. Several projects now have used CubeSats to obtain first‐of‐their‐kind observations and findings that have formed the basis for high‐profile engineering and science publications, thereby establishing without doubt the scientific value and broad utility of CubeSats. In this paper, we describe recent achievements and lessons learned from a representative selection of successful CubeSat missions with a space weather focus. We conclude that these missions were successful in part because their limited resources promoted not only mission focus but also appropriate risk‐taking for comparatively high science return. Quantitative analysis of refereed publications from these CubeSat missions and several larger missions reveals that mission outcome metrics compare favorably when publication number is normalized by mission cost or if expressed as a weighted net scientific impact of all mission publications. Plain Language Summary: Space missions using very small satellites and low resources have demonstrated they can accomplish high quality science, overcoming initial low expectations of many inside the space science community. We focus on one class of small satellites known as "CubeSats." CubeSats comprise a small number of modular cubes, each the size of a typical tissue box and weighing approximately one kg (like a pineapple). We discuss five CubeSat missions that operated during the last 10 years, each having total mission mass of three kg and total mission costs of slightly more than 1 million US dollars. These missions had focused goals targeting different aspects of space weather. For each mission, we summarize its scientific achievements and lessons learned, many of them common lessons. Larger missions have flown during this same time with overall mass ranging from hundreds to thousands of kilograms and mission costs many hundreds of thousands to over 1 billion US dollars. We compare the relative science value of these smallest and larger missions through the publications they produce in professional journals. Though CubeSat missions yield far fewer total publications compared to larger missions, the cost per publication is lower while still producing comparably high scientific impact. Key Points: Many National Science Foundation/National Aeronautics and Space Administration‐funded CubeSat missions have contributed significantly to space weather research and applications Low‐cost missions benefit from a rapid "fly learn‐modify‐refly" cycle CubeSat science productivity is comparably high to larger missions if normalized by cost or by weighted impact of refereed publications